Analysis of the chemical composition, antifungal activity and larvicidal action against Aedes aegypti larvae of the Essential Oil Cymbopogon nardus (Research, Society and Development, 2021)
The Cymbopogon nardus L. is a plant popularly known as "citronella grass", originating from Ceylon and India, used in Indonesia as a soothing and digestive tea. The essential oil of the species Cymbopogon nardus (OECN) is used in the manufacture of cosmetics and perfumes, besides having shown antimicrobial action against Escherichia coli, Salmonella spp., Pseudomonas spp., Streptococcus spp., and in addition antioxidant, anti-inflammatory. The objective of this study was to determine the larvicidal and fungicide potential of OECN extracted from the fresh leaves of C. nardus. L at the beginning of the dry season in Teresina, PI. From the OECN extracted by hydrodistillation, the actives were identified by mass gas chromatography. The larvicidal action of OECN was tested against the third and fourth larval stages of Aedes aegypti at concentrations (2.5, 5.0, 7.5 and 10 μL/20 ml) for 24 to 48 hours. Antifungal activity for Aspergillus flavus and A. parasiticus at concentrations (1.0, 2.0, 4.0 6.0 and 8.0 μL/10 mL). The OECN showed a good yield (1.0%), with 26 assets (93.2%) identified with the majority: citronelal (31.6%), geraniol (22.1%), elemol (11.8%) and citronellol (8.2%). Mortality of 100% of the larvae was observed at concentrations of 7.5 and 10.0 µl / 20 ml in 24 hours. After 48 hours 93.3% in 5.0 µl/10 ml OECN and 70% in 2.5 µl/10 ml. A. flavus showed greater sensitivity to OECN at 8.0 µl / 10 ml than A. parasiticus at concentrations. A. parasiticus was the most sensitive at concentrations of 1.0 and 2.0 µL / 10 mL. OECN has a larvicidal action and antifungal activity at the tested concentrations.